Risk Factors Associated with Overweight and Obesity in Japanese-Brazilians. (8th May 2018) - Back, Ivi R.; Oliveira, Rosana R.; Silva, Eraldo S.; Marcon, Sonia S.
Abstract : Objective . To estimate which risk factors (sociodemographic, lifestyle, and health conditions) are associated with overweight and obesity in Japanese-Brazilians. Methods . This was a cross-sectional study carried out with Japanese-Brazilians living in the southern region of Brazil. Data were collected between March and December of 2016 through a household survey addressing sociodemographic characteristics, lifestyle, and health conditions. Data were analyzed by means of logistic regression considering 95% level of significance. Results . A total of 542 Japanese-Brazilians with a mean age of 47.75 years were evaluated; 52.8% were eutrophic, 36.9% were overweight, and 10.3% were people with obesity. The following variables remained associated with overweight after adjustments; male gender (ORaj = 1.85, CI = 1.24–2.76), age range of 40–49 years (ORaj = 2.27, CI = 1.10–4.68), and 50 to 59 years (ORaj = 2.17, CI = 1.004–4.72), alcohol consumption (ORaj = 2.11, CI = 1.07–4.16), and presence of chronic disease (ORaj = 1.59, CI = 1.02–2.46). The following were independent factors associated with obesity: male gender (ORaj = 3.63, CI = 1.78–7.40), the presence of chronic disease (ORaj = 4.13, CI = 1.96–8.71), the age range of 30 to 39 years (ORaj = 4.74, CI = 1.65–13.64) and 40 to 49 years (ORaj = 2.89, CI = 1.05–7.95), and irregularly active lifestyle (ORaj = 2.73, CI = 1.12–6.69). Conclusion . The results of this study show that being a male in the age range of 30–49 years old, alcohol consumption, and presence of chronic disease are associated with overweight and obesity in Japanese-Brazilians.